Education on the Utilization of Family Medicinal Plants (TOGA) as Complementary Therapy in Anjir Serapat Muara Village - Sutrisno, Sutrisno; Norhajjah, Norhajjah; Prawira, Ivan Yudhi; Hidayat, Rahmat; Lestari, Sri; Agustini, Meti (UrbanGreen Central Media, 2025)
Indonesia’s rich biodiversity includes many Family Medicinal Plants (TOGA) as traditionally used to treat minor health issues. Family Medicinal Plants (TOGA) are medicinal plants grown at home for traditional treatment. In Anjir Serapat Muara Village, most residents grow TOGA plants but lack adequate knowledge of their use as complementary therapy. Community Education aimed to improve local understanding and utilization of TOGA to promote independent health care.The intervention had three phases: initial observation and needs assessment, educational sessions with lectures, visual aids, and booklets, and pre- and post-test evaluations. Sixty-five villagers participated in sessions held at the village hall, including interactive discussions.Before education, 60% had good knowledge and 74% used TOGA medicinally. After the program, both knowledge and utilization increased to 100%. Additionally, 86.2% already owned medicinal plants, supporting practical application.This study shows that targeted community education effectively enhances knowledge and use of family medicinal plants, leveraging local wisdom to improve health literacy and self-reliance in complementary therapy.